The Relationship Between Body Mass Index and Recurrence Risk of Stroke: A Systematic Review and Dose–Response Meta‑Analysis - Qiuxia Qian; Yuting Zhao; Xin Fan; Jialu Li; Jianxun Cao; Mengyu Yang; Longchun Hua; Xingxia Zhang; Ailing Yang; Fengwa Zhang; Yuxia Ma (Brain and Behavior)
ABSTRACT Objective To explore the relationship between body mass index (BMI) and the recurrence risk of stroke. Methods We searched databases, including the Web of Science, Cochrane Library, Embase, PubMed, Chinese Biomedical Literature (CBM), CQVIP, WanFang Database, and China National Knowledge Infrastructure (CNKI), from inception to February 2025, to collect literature on BMI and the recurrence risk of stroke. After two researchers independently screened the literature, extracted the literature data, and assessed the quality of the literature included in the study, a meta‐analysis was conducted using Stata 16.0 software, and the dose–response relationship between BMI and the recurrence risk of stroke was analyzed using generalized least squares trend estimation method (GLST) and restricted cubic spline function. Results A total of 18 studies were included, involving 165,366 patients. In terms of stroke recurrence risk, compared with normal‐weight patients, underweight patients [relative risk (RR) = 1.59, 95% confidence interval (CI) 1.33–1.90, I2 = 0%, p = 0.444] had a higher recurrence risk of stroke, whereas overweight (RR = 0.91, 95% CI 0.86–0.96, I2 = 0%, p = 0.454) and obese patients (RR = 0.89, 95% CI 0.84–0.94, I2 = 13.1%, p = 0.330) had a lower recurrence risk of stroke. The results of the linear trend show that for every unit increase in BMI, the recurrence risk of stroke decreases by 2% (RR = 0.98, 95% CI 0.96–0.99, p < 0.001). Conclusion Increased BMI is associated with a decreased recurrence risk of stroke. Underweight is a risk factor for stroke recurrence, whereas overweight and obesity are protective factors for stroke recurrence. Overweight and obesity may be beneficial for secondary prevention in stroke patients. Clinical Trial Registration Not applicable.